Corrigendum: Acute administration of MK-801 in an animal model of psychosis in rats interferes with cognitively demanding forms of behavioral flexibility on a rotating arena - Svoboda, Jan; Stankova, Anna; Entlerova, Marie; Stuchlik, Ales (Frontiers in behavioral neuroscience, 2015)
[This corrects the article on p. 75 in vol. 9, PMID: 25883558.].
Keywords: flexibility; rats; MK-801; active place avoidance; memory